Man is not created to suffer defeat - M. Bayeshanov (Peerian Journals Publishing, 2022)
In the novel of “The old man and the sea” by Ernest Hemingway it is described the difficult environment of humanity as well as his ideas and the feelings around the world. The main consideration of the novel is his confrontation with the nature, victory and interosculation with it. The main hero of the novel – the old man Santyago is unusual man who understands his life in his own risk to finish the work till to the end that he began already. He lives in believe in his future success. The readers are in delighted with his feeling of love of life, love of nature and to treat with his adversary with respect.
Keywords: adversary; treat; future; delighted